Programmes of Industrial Development 1956-61 - Planning Commission (Planning Commission, 1956)
The First Plan set comparatively modest targets for new investments in the industrial field; the emphasis was more on fuller utilisation of capacity already in existence. By and large, fuller utilisation, to the extent possible, has been achieved and idle capacity now existing is mainly out-moded capacity which could not be brought into use without extensive replacement and modernisation. In other words, the effective idle capacity currently available in major national industries like cotton and jute textiles, cement, sugar and paper is negligible. There is, however, still some idle capacity in the superphosphate, soap, vegetable oils, vanaspati and paint industries and in some engineering industries e.g., the diesel engine and radio industries, and in the re-rolling sector of steel and non-ferrous metal industries.
Government of India Planning Commission
Government of India Planning Commission